2008
DOI: 10.1007/s11069-008-9244-4
|View full text |Cite
|
Sign up to set email alerts
|

A multicriteria approach for flood risk mapping exemplified at the Mulde river, Germany

Abstract: In this paper we develop a GIS-based multicriteria flood risk assessment and mapping approach. This approach includes flood risks which are not measured in monetary terms; it shows the spatial distribution of multiple risks, and it is able to deal with uncertainties in criteria values and to show their influence on the overall flood risk assessment. Additionally, the approach can be used to show the spatial allocation of the flood effects if risk reduction measures are implemented. The approach is applied to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
160
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(173 citation statements)
references
References 21 publications
1
160
0
12
Order By: Relevance
“…Referring to the case studies reported by Brouwer and van Ek (2004), Janssen et al (2003), Penning-Rowsell et al (2003), Socher et al (2006) and Bana et al (2004), one can notice that flood risk assessment using MCA is mainly focused to evaluate the flood mitigation rather than risk mapping (Meyer et al 2009). Cowen (1988) opined that GIS can be effectively used as a decision supporting tool to address the problems related to spatially referenced data.…”
Section: Multi-criteria Analysismentioning
confidence: 99%
“…Referring to the case studies reported by Brouwer and van Ek (2004), Janssen et al (2003), Penning-Rowsell et al (2003), Socher et al (2006) and Bana et al (2004), one can notice that flood risk assessment using MCA is mainly focused to evaluate the flood mitigation rather than risk mapping (Meyer et al 2009). Cowen (1988) opined that GIS can be effectively used as a decision supporting tool to address the problems related to spatially referenced data.…”
Section: Multi-criteria Analysismentioning
confidence: 99%
“…loss of agricultural soil due to erosion, scarcity of cereals, etc.) with only few methodological approaches available for their (monetary) quantification (Dutta et al, 2003;Meyer et al, 2009). Recent events in the province of Modena (northern Italy) confirmed the relevance of this receptor within the (socio-) economic compartment with EUR 54 M of losses caused by (only) 2 days of rainfall in late January 2014 (ANSA, 2014).…”
Section: Physical/environmental Risk Assessment For Agriculturementioning
confidence: 98%
“…Potential impact on people lives is considered as the indicator of social flood hazard [15,42,43]. A combination of flood depth and velocity is used to estimate the hazard to people lives according to the taxonomy by Assistant Commissioner-Engineering and Research (ACER) [44].…”
Section: Sustainability-based Flood Hazard Mappingmentioning
confidence: 99%